PENGARUH DOSIS AQUASYM DAN INTERVAL PENYIRAMAN TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis Quineensis, Jacq) DI PRE NURSERY - Posman HP Marpaung (JURNAL AGROTEKNOSAINS, 2018)
This study was to determine the effect of aquasym doses and watering intervals on the growth od ail palm seedlings in pre nursery. The research was condueted from Oktober 2017 untik completed, in the village of mulyorejo subdistrict Sunggal of Deliserdang districk. Experiments using a randomized block design (RAK) with 2 factor 3 replications. The first factor is Dosage of Aguasym Ao = without Aguasym, A1 = 20 gr/polybag, A2=40 gr/polybag and A3 = 60 gr/polybag. The second factor is the watering interval Io=2 times days, I1=2 days, I2=3 days, I4= 4 days. Results of research conducted and after analyzed in statistik obtained that the treatment of Aquasym dose gave no signicant 40 gr/polybag (A2) showed better, tendency in all parameter observed. Treatment of the watering interval did not make a significant difference to all observed parameters, although there was a tendency that with 3 day watering. (I2) showed better plant growth on all observed parameters. The interaction between aquasym doses and watering intervals did not make a significant difference to all observed parameters, however there was a tendency that with 3-day watering intervals (I2) yielding better plant growth that other combinations.